2011
DOI: 10.4155/cli.11.67
|View full text |Cite
|
Sign up to set email alerts
|

Developing a network in a neglected area of clinical research: the UK Dermatology Clinical Trials Network

Abstract: The UK Dermatology Clinical Trials Network (UK DCTN) was established in 2002 to address our collective ignorance on the treatment of skin disease. Although started with just a good idea and goodwill, the UK DCTN has grown into a UK-wide collaborative group of over 600 members running five fully funded clinical trials. The aim of the UK DCTN is simple: to conduct high quality, independent, multicenter, randomized controlled clinical trials for the prevention or treatment of skin disease. This article describes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…This may be because the trials all addressed key questions that had been identified in previous systematic reviews [15][16][17][18] and prioritized by clinicians and patients through the UK DCTN. 19 Two of the UK DCTN trials in this survey [penicillin for recurrent cellulitis (PATCH) and doxycycline for pemphigoid (BLISTER)] dealt with inexpensive medicines that had been used for many years by some clinicians, which were thought to be beneficial but had never been tested properly. The SINS study was the first independent comparison of topical imiquimod against the reference standard of excisional surgery, which provided stable estimates of treatment responsean active comparison study that industry would not usually tackle.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the trials all addressed key questions that had been identified in previous systematic reviews [15][16][17][18] and prioritized by clinicians and patients through the UK DCTN. 19 Two of the UK DCTN trials in this survey [penicillin for recurrent cellulitis (PATCH) and doxycycline for pemphigoid (BLISTER)] dealt with inexpensive medicines that had been used for many years by some clinicians, which were thought to be beneficial but had never been tested properly. The SINS study was the first independent comparison of topical imiquimod against the reference standard of excisional surgery, which provided stable estimates of treatment responsean active comparison study that industry would not usually tackle.…”
Section: Discussionmentioning
confidence: 99%
“…As the study is funded through a Doctoral Research Fellowship, investigators are contributing on a voluntary basis as they believe this is a clinically important question that will help to improve practice, and trial drugs are prescribed through normal clinical care pathways. This recruitment model has been successfully used in other UK Dermatology Clinical Trials Network Trials [ 21 ]. An example of a study previously developed in this way for a rare skin condition is the ‘STOP GAP’ trial of prednisolone versus cyclosporin for pyoderma gangrenosum [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the juxtaposition of the CSG alongside the UK Dermatology Clinical Trials Network (UKDCTN) at the Centre of Evidence Based Dermatology in Nottingham, UK, has led to new studies initiated by the UKDCTN on the basis of research gaps identified from CSG research. As an example, the current international clinical trial of tetracycline versus prednisolone for bullous pemphigoid arose from a Cochrane Review on this topic .…”
Section: Impactmentioning
confidence: 99%